Assessment of the Symmetry of the Ground Reaction Forces in Patient with ACL Rupture during Vertical Jump - Keyvan Sharifmoradi; Arash Raji (Islamic Azad University, Hamedan Branch, 2017)
Objectives: The aim of this study was to assess the symmetry of ground reaction forces in patient with ACL rupture during vertical jump. Methods: Six men with ACLD (anterior cruciate ligament disease) participated in this study. Ground reaction forces components were assessed during Sargent jump by Kistler force plate. Data were analyzed running dependent Samples T-test and Repeated Measure in at p≤0.05. Result: Peak anterior posterior ground reaction forces were significantly greater in sound limb compared to the affected limb during landing phase (P=0.04). During landing, vertical (p=0.00) and anterior posterior (p=0.01) impulse in sound limb were significantly greater than those of affected limb. There were no significant differences between loading and unloading rates between both side in take-off and landing phases (p<0.05). Conclusion: The pattern of vertical jump ground reaction forces changes in landing phase after ACL rupture. Also, there is no difference in the impact between injured and uninjured leg in take-off phase, but there is a meaningful difference between two sides in landing phase. It is proposed that people with ACL rupture avoid repeated jumping performance because the increased impact on sound leg can put the sound leg in risk of injury. Thereafter the possibility of ACL rupture of sound leg will decrease.